The Earliest Case of Spondylocarpotarsal Synostosis Syndrome (Roman Age—2nd Century ad). (11th July 2011) - Rubini, M.; Cerroni, V.; Zaio, P.
Abstract Spondylocarpotarsal synostosis syndrome (SCT) is a rare genetic disease. It was described for the first time during the 1970s. The most relevant pathognomonic skeletal changes are vertebral malsegmentation and the fusion of the carpal and tarsal bones. This last implication can be absent in some cases. We have investigated a case of SCT in a female of about 40–45 years of age, dated to the 2nd century ad. This discovery is important for two reasons: first, SCT is not a recent disease but rather one with a very long history; second, the clinical picture of the skeletal changes (malsegmentation of some elements of the spine, fusion of carpal bones) seems not to have varied in the last 2000 years. Furthermore, the age of the Roman female shows medium–long survival in patients suffering from SCT, even in the absence of medical treatment. Copyright © 2011 John Wiley & Sons, Ltd.